Islam di Malaysia : Masuknya Agama Islam di Malaysia dan Perkembangan Pendidikan Islam di Malaysia - Lilis Sulistiawati; M Rizky Yahya; Muhamad Shoheh (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islam entered Malaysia through trade, especially by Arab, Indian and Chinese traders since the 7th century, but wider spread occurred in the 13th century through the Kingdoms of Samudera Pasai and Melaka. The Islamization process became stronger with the role of the Malay kingdoms in making Islam the official religion, establishing a sharia-based government system, and introducing Jawi writing as the main medium in education and administration.The development of Islamic education in Malaysia began with the Islamic boarding school and madrasa system which emphasized traditional religious teachings. In the colonial era, Islamic education underwent changes with the establishment of folk religious schools and modern madrasas which combined religious and academic curricula. After independence, the Malaysian government introduced a more formal Islamic education system through national religious schools, tahfiz institutions, and Islamic universities. This development was strengthened by the introduction of JAKIM, the Malaysian Ministry of Education, as well as an educational foundation that supports the integration of Islamic values ​​in the national education system. Today, Islamic education in Malaysia continues to develop through technology and innovation, ensuring it is relevant in the modern world while preserving Islamic scientific traditions.